1988
DOI: 10.1002/ptr.2650020305
|View full text |Cite
|
Sign up to set email alerts
|

The biological activity of eugenol, a major constituent of nutmeg (Myristica fragrans): Studies on prostaglandins, the intestine and other tissues

Abstract: Studies have been made of eugenol on isolated tissues from man and laboratory animals, and on rats in uiuo. Eugenol inhibited prostaglandin synthesis, and reduced the tone of isolated gut muscle and myometrium. With rats in uiuo, the compound reduced the rate of intestinal transit, the intestinal accumulation of fluid induced by prostaglandin E,, and the diarrhoea induced by castor oil. Eugenol showed anti-inflammatory activity in the rat paw carrageenin oedema test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…4-Vinylguaiacol (4) (IC50 = 18 pM), which is an analogue of eugenol, was about half as potent as eugenol. Eugenol, a phenolic constituent of cloves (Syzygium aroma ticurn) arid nutmegs (Myristicafragrans), is a well-known inhibitor of prostaglandin synthesis and also possesses anti-inflammatory activity in carrageenan-induced rat paw edema (13)(14)(15). Eugenol and guaiacol are also reported to inhibit leukocyte chemotaxis and prevent the production of oxygen free-radicals by leukocytes (16).…”
Section: Resultsmentioning
confidence: 99%
“…4-Vinylguaiacol (4) (IC50 = 18 pM), which is an analogue of eugenol, was about half as potent as eugenol. Eugenol, a phenolic constituent of cloves (Syzygium aroma ticurn) arid nutmegs (Myristicafragrans), is a well-known inhibitor of prostaglandin synthesis and also possesses anti-inflammatory activity in carrageenan-induced rat paw edema (13)(14)(15). Eugenol and guaiacol are also reported to inhibit leukocyte chemotaxis and prevent the production of oxygen free-radicals by leukocytes (16).…”
Section: Resultsmentioning
confidence: 99%
“…The results of an in vivo study on rats demonstrated that eugenol reduced diarrhoea induced by castor oil, the tone of isolated gut muscle and myometrium, the rate of intestinal transit and the intestinal accumulation of fluid induced by PGE 2 [ 91 ]. In order to investigate some of the mechanisms involved in the spasmolytic and relaxant effects of eugenol, the effects of eugenol on contractions of isolated rat ileum induced by electrical field stimulation (EFS) were studied.…”
Section: Other Pharmacological Propertiesmentioning
confidence: 99%
“…Recently, the pharmacological actions of nutmeg have been examined, and demonstrated toxicity on the central nervous system (Edward et al. 1961;Payne, 1963) and inhibition of prostaglandin synthesis (Rasheed et al, 1984;Bennet et al, 1988).…”
Section: Introductionmentioning
confidence: 98%